Pediatric Multiple Sclerosis and Cognition: A Review of Clinical, Neuropsychologic, and Neuroradiologic Features - Ozgul Ekmekci (Behavioural Neurology)
Multiple sclerosis (MS) is an inflammatory demyelinating and neurodegenerative disease. Although cognitive impairment has been well established in adult patients with MS, its occurrence in patients with pediatric-onset MS has recently been reported. In this review, I discuss the main features of cognitive impairment in pediatric MS as determined by long-term follow-up studies, neuropsychiatric test batteries, and the results of neuroradiological imaging studies that investigated the pathogenesis of pediatric MS. The most commonly affected cognitive domains in adults are attention, processing speed, and visuomotor skills; language and intelligence are also affected in pediatric MS. A young age at disease onset is the strongest risk factor for these impairments, which may be due to the effect of inflammatory demyelination and neurodegeneration on the developing central nervous system and neural networks in children. Cognitive impairment has long-term effects on patients’ academic life and the quality of their social life. Therefore, all patients with pediatric MS should be screened and monitored for cognitive impairment. This review also highlights the need for neuropsychological test batteries that assess different cognitive domains in children and adolescents with multiple sclerosis and for cognitive rehabilitation programs to improve the quality of their academic and social life.